Should alectinib or ceritinib be given as first line therapy for ALK positive non-small cell lung cancer patients instead of crizotinib? - Peters, Godefridus J.; Muller, Ittai B.; Giovannetti, Elisa (Translational Cancer Research; Vol 6, Supplement 6 (August 29, 2017): Translational Cancer Research, 2017)
For patients with ALK positive non-small cell lung cancer (NSCLC), various treatment options are currently available. Crizotinib was the first drug with proven activity for these patients (1), followed by ceritinib (2,3) and alectinib (4-6) for patients progressing on crizotinib treatment. Most recently brigatinib was also approved for crizotinib-resistant patients, while lorlatinib received breakthrough status from the FDA and may be the next ALK inhibitor to be approved. These alternatives appear to be active against mutations in the ALK gene associated with crizotinib resistance.